Perinatal folate supply: relevance in health outcome parameters - Fekete, Katalin (Matern Child Nutr, 2010)
The importance of physiological supply of folate is well recognized in human health; the crucial roles of folate in one‐carbon metabolism for physiological DNA synthesis and cell division, as well as in the conversion of homocysteine (Hcy) to methionine, and subsequently, to S‐adenosylmethionine, have been convincingly demonstrated. Improved folate status may reduce the risk of macrocytic anaemia, cardiovascular diseases, neuropsychiatric disorders and adverse pregnancy outcomes. Inadequate folate status results in a decrease in the methylation cycle and in increased blood levels of the neurotoxic Hcy. The aim of this review is to provide insight into the influence of folate status on pregnancy health outcomes, and to consider increasing evidence of a link between the extent of genome/epigenome damage and elevated risk for adverse obstetrical endpoints. Pregnant women are at risk for folate insufficiency because of the increased need for folate for rapid fetal growth, placental development and enlargement of the uterus. Inadequate folate status may cause fetal malformations, impaired fetal growth, pre‐term delivery and maternal anaemia. Even some diseases of the placenta may arise from folate deficiencies. Fetal growth seems to be vulnerable to maternal folate status during the periconception period, because it has the potential to affect both the closure of the neural tube and several epigenetic mechanisms within the placenta and the fetus. Mainly on the basis of the well recognized link between maternal folate status and fetal neural tube defects, women are advised to receive folic acid supplement during the periconceptional period. Because an adequate folate supply seems to play an important role in the implantation and development of the placenta and in improving endothelial function, folic acid supplementation in the late first trimester or early second trimester might also be beneficial.